Clinical T4b Squamous Cell Carcinoma Resection With Hemimandibulectomy and Temporomandibular Joint Reconstruction With Bridging Plate and Modified Dautrey Procedure. Issue 3 (21st May 2022) - Shih, Hao; Lee, Jian-Jr; Lin, Yu-Ting
Abstract : Abstract: Clinical T4b oral squamous cell carcinoma is traditionally considered nonoperable. We present a case of right mandibular squamous cell carcinoma (P T4bN0M0, stage IVB). The tumor had extended to the right mandibular condylar head and masticatory space. The patient received right modified radical neck dissection and radical operation with hemimandibulectomy to remove the right mandibular condyle. Then, we reconstructed the resected portion with an anterior lateral thigh free flap and bridging plate, which was bent to form an artificial condyle and fixed using the modified Dautrey procedure. The patient had stable postoperative occlusion and normal hinge movement of the temporomandibular joint. After postoperative concurrent chemotherapy and radiotherapy, the patient is under regular out patient department follow-up with satisfactory jaw function and oral intake.